Strategy to Improve Service Quality in Service UMKM At “Berkah Rizki Photocopy” Gunung Pasir Jaya, A Village in East Lampung, Lampung Province - Daud, Syahril; Dewita, Kadek Putri; Lediestiani, Silvi; Bobiyana, Pandya I Ketut (FKIP Universitas Lampung, 2024)
Increasing competition in the MSME sector requires actors to continue to innovate, one of which is in terms of service quality. This research specifically analyzes the strategies implemented by UMKM Berkah Rizki Photocopy located in Gunung Pasir Jaya, One Village Udik, East Lampung, in improving service quality to achieve customer satisfaction and loyalty. Through a qualitative approach with case studies, this research reveals that MSME Berkah Rizki Photocopy implements several strategies, such as improving product quality, speed of service, and personalization of service. These findings indicate that these efforts are effective in increasing customer satisfaction and ultimately encouraging the creation of customer loyalty. This research contributes to the development of knowledge in the field of management, especially in MSMEs, as well as providing recommendations for other MSME actors in improving service quality.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.241-250